Monocytes complexed to platelets differentiate into functionally deficient dendritic cells. Issue 4 (14th July 2020) - Singh, Meera V.; Suwunnakorn, Sumanun; Simpson, Sydney R.; Weber, Emily A.; Singh, Vir B.; Kalinski, Pawel; Maggirwar, Sanjay B.
Abstract: In addition to their role in hemostasis, platelets store numerous immunoregulatory molecules such as CD40L, TGFβ, β2‐microglobulin, and IL‐1β and release them upon activation. Previous studies indicate that activated platelets form transient complexes with monocytes, especially in HIV infected individuals and induce a proinflammatory monocyte phenotype. Because monocytes can act as precursors of dendritic cells (DCs) during infection/inflammation as well as for generation of DC‐based vaccine therapies, we evaluated the impact of activated platelets on monocyte differentiation into DCs. We observed that in vitro cultured DCs derived from platelet‐monocyte complexes (PMCs) exhibit reduced levels of molecules critical to DC function (CD206, dendritic cell‐specific intercellular adhesion molecule‐3‐grabbing nonintegrin, CD80, CD86, CCR7) and reduced antigen uptake capacity. DCs derived from PMCs also showed reduced ability to activate naïve CD4 + and CD8 + T cells, and secrete IL‐12p70 in response to CD40L stimulation, resulting in decreased ability to promote type‐1 immune responses to HIV antigens. Our results indicate that formation of complexes with activated platelets can suppress the development of functional DCs from such monocytes. Disruption of PMCs in vivo via antiplatelet drugs such as Clopidogrel/Prasugrel or the application of platelet‐free monocytes for DCs generation in vitro, may be used to enhance immunization and augment the immune control of HIV. Graphical Abstract: Dendritic cells derived from monocytes complexed to platelets are functionally defective and can negatively impact induction of anti‐HIV immune responses.